Collaborative Governance dalam Mewujudkan Zero to Landfill di Kota Cimahi Tahun 2023-2024 - Agus Taryana; Silmy Putri Mahandry (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2025)
(Collaborative Governance in Waste Management in Cimahi City in 2023-2024) The research aims to analyze the dynamics of collaborative governance between the government, private sector, academics, community, and media in waste management efforts in Cimahi City in 2023-2024. Although many waste management programs have been implemented, the relational processes between actors often determine their success or failure. This research uses a qualitative descriptive approach, gathering data through in-depth interviews with representatives government, private sector, academic, community, media, and the public, supported by observations and document analysis. The collaborative governance model by Ansell and Gash is used as an analytical tool to dissect the dynamics occurring on the ground. The results of the study show that the collaboration process has not been effective due to several obstacles. The main issues include the absence of a Waste-Free Communication Forum or a formal forum with all actors involved; the difficulty of building strong trust due to lingering doubts between the community and one of the private sector actors, as well as between the community and waste management officials; the difficulty in unifying perspectives on the importance of waste sorting with the community; and the limited infrastructure, land, and human resources, which hinder the implementation of waste management itself. Therefore, in order for waste management to run optimally and sustainably, it is necessary to have a forum for joint discussions and more intensive communication as the main cornerstone in this collaboration process so that the next stages can also run more effectively. Abstrak Penelitian ini bertujuan untuk menganalisis dinamika tata kelola kolaboratif antara pemerintah, sektor swasta, akademisi, masyarakat, dan media dalam upaya pengelolaan sampah di Kota Cimahi pada tahun 2023-2024. Meskipun, banyak program pengelolaan sampah telah dilaksanakan, proses relasional antara para pemangku kepentingan seringkali menentukan keberhasilan atau kegagalan program tersebut. Penelitian ini mengadopsi pendekatan deskriptif kualitatif dengan pengumpulan data dilakukan melalui wawancara secara mendalam dengan perwakilan pemerintah, sektor swasta, akademisi, masyarakat, media, dan publik, didukung oleh observasi dan analisis dokumen. Model tata kelola kolaboratif oleh Ansell dan Gash digunakan sebagai alat analitis untuk menganalisis dinamika yang terjadi di lapangan.  Hasil penelitian menunjukkan bahwa proses kolaborasi belum efektif akibat beberapa hambatan. Masalah utama meliputi ketidakhadiran Forum Komunikasi Tanpa Sampah atau forum formal yang melibatkan semua pihak terkait; kesulitan dalam membangun kepercayaan yang kuat akibat keraguan yang masih ada antara masyarakat dan salah satu aktor sektor swasta, serta antara masyarakat dan pejabat pengelolaan sampah; kesulitan dalam menyatukan perspektif mengenai pentingnya pemilahan sampah dengan masyarakat; dan keterbatasan infrastruktur, lahan, dan sumber daya manusia, yang menghambat implementasi pengelolaan sampah itu sendiri. Oleh karena itu, agar pengelolaan sampah dapat berjalan optimal dan berkelanjutan, diperlukan forum untuk diskusi bersama dan komunikasi yang lebih intensif sebagai landasan utama dalam proses kolaborasi ini agar tahap-tahap selanjutnya juga dapat berjalan lebih efektif